Interphotoreceptor Retinoid‐Binding Protein Protects Retinoids from Photodegradation. (10th February 2015) - Gonzalez‐Fernandez, Federico; Betts‐Obregon, Brandi; Yust, Brian; Mimun, Joshua; Sung, Dongjin; Sardar, Dhiraj; Tsin, Andrew T.
Abstract Retinol degrades rapidly in light into a variety of photoproducts. It is remarkable that visual cycle retinoids can evade photodegradation as they are exchanged between the photoreceptors, retinal pigment epithelium and Müller glia. Within the interphotoreceptor matrix, all‐trans retinol, 11‐cis retinol and retinal are bound by interphotoreceptor retinoid‐binding protein (IRBP). Apart from its role in retinoid trafficking and targeting, could IRBP have a photoprotective function? HPLC was used to evaluate the ability of IRBP to protect all‐trans and 11‐cis retinols from photodegradation when exposed to incandescent light (0 to 8842 μW cm−2); time periods of 0–60 min, and bIRBP: retinol molar ratios of 1:1 to 1:5. bIRBP afforded a significant prevention of both all‐trans and 11‐cis retinol to rapid photodegradation. The effect was significant over the entire light intensity range tested, and extended to the bIRBP: retinol ratio 1:5. In view of the continual exposure of the retina to light, and the high oxidative stress in the outer retina, our results suggest IRBP may have an important protective role in the visual cycle by reducing photodegradation of all‐trans and 11‐cis retinols. This role of IRBP is particularly relevant in the high flux conditions of the cone visual cycle.